Factor Analysis of Training, Knowledge, Supervision, and Unsafe Actions on Occupational Accidents at PT X - Noor Intan Ramadhani (Universitas Airlangga, 2019)
Introduction: Industrial accidents are accidents occurring in the workplace, especially in the industrial environment. According to the data, the occupational accidents at PT X in RKC (raw mill, kiln, cooler) Operational Section of Slag Production are still found annually. From 2015 to 2017, there had been nine occupational accidents recorded. There was one occupational accident in 2015, five occurrences in 2016, and three occurrences in 2017. This study aimed to analyze the factors of supervision, training, knowledge, and unsafe actions that can lead to occupational accidents suffered by the workers in RKC Operational Section of Slag Production at PT X. Methods: This study was a cross-sectional study with a population of 19 people by implementing the descriptive test analysis to describe the percentage of each observed dependent variable. Results: This study revealed that 78.9% of the workers claimed that the supervision was good, 73.7% agreed that the training was good, 57.9% agreed that they had good knowledge, and 52.6% claimed to conduct unsafe actions in moderate level. Conclusion: the factors of supervision, training, and knowledge were influential to the occurrence of occupational accidents, yet they remained within the tolerable level since almost all workers performed in the good category in those categories. On the other hand, unsafe actions had a considerable influence on the occurrence of occupational safety and health since the majority of the workers performed unsafe actions moderately. Keywords: factor analysis, occupational accidents, unsafe actions